The effect of preoperative total antioxidant capacity on short-term outcomes after kerato-lenticule extraction surgery - Chia-Yi Lee; Hung-Chi Chen; Shun-Fa Yang; Yi-Jen Hsueh; Jing-Yang Huang; Chao-Kai Chang (Scientific Reports, 2025)
Abstract To evaluate influence of total antioxidant capacity expression (TAC) on outcome of kerato-lenticule extraction (KLEx). A prospective non-randomized trial was conducted and patients received KLEx were categorized via TAC concentration. A total of 56 and 36 eyes were enrolled into the low TAC and high TAC groups. The main outcomes are the postoperative un-corrected visual acuity (UCVA), refraction and superficial keratitis between groups. The generalized liner model was applied for statistical analysis. One month after the KLEx surgery, the UCVA was significantly higher in the high TAC group (P = 0.028), and low TAC group associated with superficial keratitis risk compared to high TAC group (P = 0.035). The trends of TAC and ascorbic acid (AA) decrements were more significant in the low TAC group (both P < 0.05). Low TAC population and old age correlated to poor UCVA (both P < 0.05) while the thick CCT correlated to better UCVA (P = 0.030). Besides, the low TAC population (P = 0.032) correlated to higher superficial keratitis rate, while old age (P = 0.018) correlated to lower superficial keratitis rate. The presence of low TAC expression correlated to worse UCVA and higher risk of superficial keratitis after KLEx.